Early cortical atrophy is related to depression in patients with neuropathologically confirmed Parkinson's disease - Backman Emmilotta A.; Luntamo Laura; Parkkola Riitta; Koikkalainen Juha; Gardberg Maria; Kaasinen Valtteri (Elsevier B.V., 2025)
Objective
Depression is a common comorbidity in Parkinson's disease (PD) and other synucleinopathies. In non-PD geriatric patients, cortical atrophy has previously been connected to depression. Here, we investigated cortical atrophy and vascular white matter hyperintensities (WMHs) in autopsy-confirmed parkinsonism patients with the focus on clinical depression.
Methods
The sample consisted of 50 patients with a postmortem confirmed neuropathological diagnosis (30 Parkinson's disease [PD], 10 progressive supranuclear palsy [PSP] and 10 multiple system atrophy [MSA]). Each patient had been scanned with brain computerized tomography (CT) antemortem (median motor symptom duration at scanning = 3.0 years), and 19 patients were scanned again after a mean interval of 2.7 years. Medial temporal atrophy (MTA), global cortical atrophy (GCA) and WMHs were evaluated computationally from CT scans using an image quantification tool based on convolutional neural networks. Depression and other clinical parameters were recorded from patient files.
Results
Depression was associated with increased MTA after controlling for diagnosis, age, symptom duration, and cognition (p = 0.006). A similar finding was observed with GCA (p = 0.017) but not with WMH (p = 0.47). In PD patients alone, the result was confirmed for MTA (p = 0.021) with the same covariates. In the longitudinal analysis, GCA change per year was more severe in depressed patients than in nondepressed patients (p = 0.029).
Conclusions
Early medial temporal and global cortical atrophy, as detected with automated analysis of CT-images using convolutional neural networks, is associated with clinical depression in parkinsonism patients. Global cortical atrophy seems to progress faster in depressed patients.